ANALISIS PENGGUNAAN BAHASA INDONESIA DALAM INTERAKSI GURU DENGAN SISWA PADA AKTIVITAS PEMBELAJARAN DI KELAS IV MADRASAH IBTIDAIYAH 8 MACCINI KOTA MAKASSAR - Sri Asrawati Nur; Ratnawati; Ika Zulfika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of Indonesian language in terms of representative, directive, expressive, commissive, and declarative speech acts in learning interactions in Grade IV at Madrasah Ibtidaiyah Muhammadiyah 8 Maccini, Makassar City. This research employed a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The data sources consisted of one teacher and twenty fourth-grade students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was tested using triangulation and member checking. The results showed that the use of Indonesian in learning interactions was communicative and effective through five types of speech acts. In the preliminary stage, interactions were dominated by representative and directive speech acts. In the core activities, speech acts became more varied and encouraged student participation. In the closing stage, the teacher used representative, expressive, directive, and declarative speech acts. Observation results indicated an improvement in the use of Indonesian from a moderate to a very good category, creating effective communication and a conducive learning environment